Efforts To Increase Achievement Of Ips Learning Through The Method Of Giving Tasks As Learning Independence In Students Class Vi Sdn 14 Lubuk Aur - Mardarizon Mardarizon (Jurnal Ilmiah Pendidikan Scholastic, 2017)
School education has an important role in improving the quality of human resources. School education is a process that involves educators, teaching materials, and learners. "Educators and education personnel are obliged to create a meaningful, fun, creative, dynamic and dialogical atmosphere of conduct, and professionally committed to improving education" (Sisdiknas 2003: 22). In creating meaningful educational background then in every learning must use appropriate strategies and learning approach so that the outcome of the learning is in accordance with the goals we want. Based on the facts, grade 6 students are very interested in learning in school either Mathematics, Indonesian Science or any other field of study, as evidenced by each student's enthusiastic learning activity is quite high and the ability to do the problem gets pretty good (average 6.4). After students learn more formally, students start learning difficulties either Mathematics, Indonesian or Science so that the higher the class of learning results decreases.